A Tiered Approach to Trauma Education in the Emergency Department. Issue 5 (September 2018) - Lee, Donna B.; Battle, Deb
Abstract : Although trauma centers are required to provide trauma education to nurses caring for trauma patients, there are no clearly defined standards for this education. In an effort to improve emergency department (ED) trauma nursing care, a tiered approach to ED trauma education (basic, intermediate, and advanced) was developed to provide specialized trauma education to a larger number of ED nurses at a Level II trauma center in Georgia. This tiered approach to ED trauma nurse education has resulted in the ability to quickly activate multiple trauma teams that work together competently and efficiently, leading to improved patient care and development of competent ED trauma nurses.